INVESTIGASI PEMANFAATAN LEARNING MANAGEMENT SYSTEM MOODLE UNTUK PEMBELAJARAN DI INDONESIA MENGGUNAKAN BIBLIOMETRIC ANALYSIS - Della Maulidiya (Computer and Informatics Education Review, 2022)
Efforts to comprehensively integrate technology and pedagogy into the learning environment, including classroom and virtual learning, have encouraged the emergence of electronic learning (e-learning), allowing students to learn anything without the limits of place and time. E-learning to be well organized requires a Learning Management System (LMS), one of which is Moodle. Moodle's potential prompted a great deal of research, resulting in so many articles that it was possible to evaluate its potential and application gaps in Indonesia. This research uses bibliometric analysis based on 209 articles indexed in Scopus for 2010 - 2022 to investigate how Moodle utilized in Indonesia. The bibliometric analysis's findings indicate that e-learning, online learning, and blended learning will continue to be the main topics of Moodle use in Indonesia. These three topics are connected by blended learning, which combines in-person instruction with online instruction. On the other hand, there is spaces to establish specialized topics within the three main themes, such as using Moodle to improve learning activities and processes, or using learning analytics to raise motivation and improve learning outcomes and achievement. Another finding is that Moodle is primarily used at the higher education. Therefore, more research is required to determine the elements to consider before Moodle is adopted at the elementary, secondary, and higher schools.